Monitoramento da geração elétrica e viabilidade econômica de um sistema fotovoltaico instalado em dois aviários em Tupãssi – PR - Primieri, Bianca Fiori (2019)
The sustainable ways of generating electricity, in the circumstance that partially or totally satisfies a demand, are in focus in the world market due to the needs of attending more consumers with fewer resources and to reduce the environmental impact caused. The focus of this study is the monitoring of electric power generation from grid - connected photovoltaic generators that supply, in a complete or non - existent manner, two Dark House aviaries located in the western region of Paraná, in Tupãssi - PR, as well as the analysis of economic viability. In order to do so, it was necessary to collect data of effective generation of the photovoltaic devices under the influence of local solar irradiation. In the economic evaluation, the electric energy consumption data was collected through the utility's billing records, to be used in multi-index calculations (VPL, TIR and Discounted Payback). The monitored year, 2018, was atypical for having a significant amount of days with closed sky and consecutively a small electricity production, therefore, it was necessary to carry out a simulation of the production of electric energy for a typical year, based on the historical averages of the local solar irradiance. The facility supplies the energy demand of the aviaries in 7 of the 12 months for the year 2018, for a typical year, that number goes up to 10 of 12 months. The month with the highest generation of electricity was April to 2018 and December in the typical year. Checking the typical clear skies days of summer and winter, it is confirmed that the panels do not operate at their maximum capacity during all months of the year, since between winter and summer there is a production difference of 12.62 kW per day. The annual cost savings of energy bills between 2017 and 2018 was R$ 33,198.89. Between 2017 and a typical year, the economy rose to R$ 38,746.89. The PBD tool indicated the economic unfeasibility of the project, being its turnaround time at 19 years. The other two parameters evaluated (VPL and TIR) inform the feasibility of the system. For each additional atypical year presented during the project, your PBD increases by one year. This study was financed in part by he Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) – Finance Code 001.